2014
DOI: 10.1002/pc.23062
|View full text |Cite
|
Sign up to set email alerts
|

Controllable preparation and heavy‐metal‐ion adsorption of lignosulfonate‐polypyrrole composite nanosorbent

Abstract: Lignosulfonate‐polypyrrole (LS‐PPY) composite nanospheres were prepared facilely via an in situ polymerization of pyrrole monomers in the presence of lignosulfonate as a dispersant and ammonium persulfate as an oxidant. The LS‐PPY composite was characterized with Fourier Transform infrared spectroscopy (FTIR), thermogravimetric analysis, wide‐angle X‐ray diffraction (XRD), scanning electron microscopy (SEM), field‐emission SEM, and transmission electron microscopy. Uniform LS‐PPY solid composite nanospheres wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…The size of the LS‐PANi particles decreased after modification of bare PANi with LS, increasing their surface area and the number of adsorption sites. Similarly, Luo and Lü synthesized LS–PPy composite nanospheres by an in situ polymerization of pyrrole monomers in the presence of LS . The LS–PPy nanospheres exhibited a uniform size, with an average diameter of 154 nm, which possessed excellent absorption capacities for Ag + (759.3 mg g −1 ) and Pb 2+ ions (207.5 mg g −1 ) from aqueous solutions.…”
Section: Lignin‐based Materials For Environmental Remediationmentioning
confidence: 99%
“…The size of the LS‐PANi particles decreased after modification of bare PANi with LS, increasing their surface area and the number of adsorption sites. Similarly, Luo and Lü synthesized LS–PPy composite nanospheres by an in situ polymerization of pyrrole monomers in the presence of LS . The LS–PPy nanospheres exhibited a uniform size, with an average diameter of 154 nm, which possessed excellent absorption capacities for Ag + (759.3 mg g −1 ) and Pb 2+ ions (207.5 mg g −1 ) from aqueous solutions.…”
Section: Lignin‐based Materials For Environmental Remediationmentioning
confidence: 99%
“…It is more intriguing to explore the possibility of extending the application of this conducting polymer. Recently, some studies have found that PPy can be used as an efficient absorbent for removal of heavy metal ions from waste water owing to their rich functional groups . However, to some extent, the separation of PPy absorbent is difficult.…”
Section: Introductionmentioning
confidence: 95%
“…e coating of PPy can avoid agglomeration and oxidation of MNPs. Furthermore, PPy has good adsorption properties for Cr(VI) from wastewater owing to their rich functional groups and environmental stability [17][18][19].…”
Section: Introductionmentioning
confidence: 99%